Effect of obesity on ecocardiographic parameters and vertebral heart size (VHS) in cats - De Souza, Fúlvia Bueno [UNESP]; Golino, Danilo Velazquez [UNESP]; Bonatelli, Shayra Peruch [UNESP]; Alfonso, Angélica [UNESP]; Mamprim, Maria Jaqueline [UNESP]; De Carvalho Balieiro, Júlio Cesar; Melchert, Alessandra [UNESP]; Guimarães-Okamoto, Priscylla Tatiana Chalfun [UNESP]; Lourenço, Maria Lucia Gomes [UNESP] (Universidade Estadual de Londrina, 2020)
The objective of this study was to correlate cardiovascular parameters with obesity in adult cats. Forty mixed-breed cats (20 obese and 20 controls) underwent echocardiographic measurements and thoracic radiography to establish a relationship between the obtained data and the body condition score (BCS), body mass index (BMI), and vertebral heart size (VHS). Systolic arterial pressure (SAP) was also studied in 15 obese cats. Compared to the control cats, obese cats presented higher VHS values across several measurements, but among the echocardiographic parameters, only the difference in the left ventricular free wall at diastole was statistically significant. A positive relationship was established between body weight, left ventricular internal diameter at diastole, and left ventricular free wall at diastole. Positive relationships were also observed between BMI and diameter of the aorta, BCS and the left ventricular free wall at diastole, VHS and the left atrium, and the left atrial to aortic root diameter ratio and the left ventricular internal diameter at diastole. SAP was higher in obese cats and presented a positive correlation with body weight. Obesity correlated with an increase in SAP and with some echocardiographic and radiographic cardiac measurements in adult cats. Further studies are needed to better assess the effects of obesity on the cardiovascular system of cats and to reassess the parameters related to body weight and condition.
Efeito da obesidade sobre parâmetros ecocardiográficos e VHS em gatos
Keywords: Body weight; Echocardiography; Feline; Thoracic radiography